1996
DOI: 10.1107/s0907444995011115
|View full text |Cite
|
Sign up to set email alerts
|

New parameters for the refinement of nucleic acid-containing structures

Abstract: Structures at atomic resolution (up to 1.0,&) which contain bases, sugars or the phosphodiester linkage, were selected from the Nucleic Acid Database or the Cambridge Structural Database to build a nucleic acid dictionary from X-ray refined structures. The dictionary consists of the average values for bond distances, bond angles and dihedral angles. The variance of the sample is used to provide information about the expected r.m.s, deviations of the refined parameters. A dictionary was constructed for refineme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
255
1
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(264 citation statements)
references
References 8 publications
3
255
1
2
Order By: Relevance
“…The Web resources also include a set of atomic coordinates for each of the 46 defined suite conformers (plus the eight ''wannabe'' conformers described in the Materials and Methods), with close to ideal bond lengths and angles (Gelbin et al 1996;Parkinson et al 1996). Their construction is described in the Materials and Methods section, producing clash-free models with dihedral angles very close to the mean values and conformations within the main grouping of typical examples for each suite conformer.…”
Section: Consensus Clusters and Meansmentioning
confidence: 99%
See 2 more Smart Citations
“…The Web resources also include a set of atomic coordinates for each of the 46 defined suite conformers (plus the eight ''wannabe'' conformers described in the Materials and Methods), with close to ideal bond lengths and angles (Gelbin et al 1996;Parkinson et al 1996). Their construction is described in the Materials and Methods section, producing clash-free models with dihedral angles very close to the mean values and conformations within the main grouping of typical examples for each suite conformer.…”
Section: Consensus Clusters and Meansmentioning
confidence: 99%
“…However, simply setting bond lengths and angles to accepted values (Parkinson et al 1996) and dihedral angles to their cluster-mean values (Table 1) gives acceptable models for only a minority of the conformers. Some conformer clusters spread only slightly in backbone dihedrals or backbone atom positions, but show subclusters in base positioning; for instance, 7r suites can have the second base either at a 70°angle to the first (as in the kink-turn rr0082/1S72 0 262 representative example) or parallel to it (as in the intercalated rr0082/1S72 0 776).…”
Section: Representative Examples and Idealized Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…E-mail: miha.andrejasic@ijs.si http://pury.ijs.si/ Keywords: macromolecular structure refinement, structure determination using X-ray diffraction; topology The paper of Engh and Huber (1991) [1] with description of accurate geometrical parameters of amino acid residues has set a new standard in macromolecular crystallography. A similar step forward in the area of nucleic acids was made by Parkinson et al (1996) [2]. With the increasing number of macromolecular structures also complexes with "hetero" ligands and their variety is growing.…”
Section: Ms07 P05 Purymentioning
confidence: 99%
“…XPLOR 14 and its successor, CNS, 15 have proven to be successful in RNA structural refinement, especially when used with the new nucleic acid parameter library produced by Helen Berman and co-workers from the Nucleic Acids Structural Database. 16 It is generally recommended that the charges on the phosphates be reduced or set to zero during simulated annealing molecular dynamics refinement, because the counterion screening environment that neutralizes the RNA cannot be modeled readily. In practice, we have found that this does not seem to make an appreciable difference in the course of refinement, perhaps because the constraint of the electron density overcomes the potential electrostatic repulsion of the phosphate backbone in the model structure.…”
Section: Structural Determination By Isomorphous Replacementmentioning
confidence: 99%